Unraveling the neuroprotective role of TUDCA in Parkinson´s disease - Fonseca, Inês Martins Ribeiro da (2015)
Accumulating evidence suggests that mitochondrial dysfunction play a central role in Parkinson’s disease (PD). Evidence is based on the identification of PD-associated mutations in genes that affect mitochondrial function, such as phosphatase and tensin homolog (PTEN)-induced putative kinase 1 (PINK1) and parkin. This was further reinforced by the discovery that exposure to 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), a mitochondrial complex I inhibitor, leads to clinical symptoms similar to sporadic PD. Thus, one therapeutic approach that has recently arisen in PD research is the selective clearance of damaged mitochondria by mitophagy. The bile acid tauroursodeoxycholic acid (TUDCA) is an anti-apoptotic molecule shown to interfere with the mitochondrial pathway of cell death. Importantly, TUDCA was demonstrated to protect against MPTP-induced neurodegeneration in mice, but the mechanisms involved are still unknown. Herein we investigate whether autophagy/mitophagy and mitochondrial biogenesis are part of TUDCA-mediated neuroprotection and discuss the molecular mechanisms involved, using two different models of PD, C57B/L6 mice and SH-SY5Y neuroblastoma cells treated with TUDCA and/or MPTP/MPP+. Our preliminary results reveal that in mice brain, TUDCA induced microtubule-associated protein 1 light chain 3 (LC3) lipidation, and increased voltage-dependent anion channel (VDAC), full length PINK1 and parkin protein expression, thereby suggesting that autophagy/mitophagy and mitochondrial biogenesis are part of TUDCA-mediated neuroprotection. In SH-SY5Y cells, TUDCA prevents MPP+-induced cell death and mitochondrial damage. Moreover, this bile acid was also shown to modulate parkin phosphorylation, and parkin expression levels in the presence of MPP+. Importantly, modulation of parkin was accompanied by increased levels of autophagy. Impaired mitochondrial turnover has been associated to PD, thus, mitochondrial protective agents represent an attractive direction for the development of new therapeutic drugs. Our results point to the pharmacological up-regulation of mitochondrial turnover by TUDCA as a novel neuroprotective mechanism of this molecule, and contribute to the validation of TUDCA clinical application in PD.